Applications Data Warehouse for Sales Analysis Based on Multidimensional Modeling (MDM) and Star Schema Design - F. , Ryan; R. , Fitrah (International Journal of Psychosocial Rehabilitation, 2020)
The data warehouse is a collection of the data used to support strategic decision-making process in an organization. This paper will discuss the design of the data warehouse in one of the industry in sales (distribution sales) of the start of the phase of data collection, analysis of business needs and information, data selection and design of data warehouse, data loading into data warehouse and the later displaying information to end user. By implementing a multidimensional modeling (MDM) of a data warehouse is built based on the method of OLAP (Online Analytical Processing) and can be displayed with the star schema design, to produce information that can analyze the sales data accurately, which can assist the company in taking decisions right appropriately and efficiently.